PEMANFATAN LIMBAH BIOMASSA MENJADI SUMBER ENERGI ALTERNATIF - suhartoyo suhartoyo suhartoyo; Yulianto Kristiawan (Universitas Muria Kudus, 2020)
This research aims to produce renewable fuel from biomass waste which has been neglected and not yet used optimally. Cashew nuts are an example of biomass that is commonly found in Indonesia. Cashew kernel shells contain a lot of new oil only for coloring. Cashew nut shells are processed into renewable energy by making briquettes. The making of briquettes begins with the carbonization process at a temperature of 350oC for 5 hours. Then to improve the quality, it is mixed with waste in the form of small pieces and sawdust of teak wood. From the tests that have been carried out, it has resulted in more cashew nut shell charcoal content, the initial flame is easier but it is wasteful of fuel because it quickly turns into ash because the cashew seed shell contains a lot of phenolic compound oil. The calorific value greatly affects the fast and slow rate of boiling and the amount of briquette raw material needed. the more cashew nut shell charcoal, the more fuel it needs to boil 1 liter of water, because cashew nut shells burn quickly, so they quickly turn to ash. From the test, it was found that the variation in the consumption of the smallest and fastest use of fuel in boiling water was a variation of the briquette mixture of 15% cashew shell charcoal: 75% wood charcoal, boiling 1 liter of water only takes 18 minutes, and only requires 268 grams of briquettes.